2023
DOI: 10.1111/aje.13110
|View full text |Cite
|
Sign up to set email alerts
|

Impact of land use patterns on bee communities in the north of Côte d'Ivoire (West Africa)

Abstract: Natural and protected area degradation constitutes a threat to bee communities and could decrease crop yield by reducing bee pollination effectiveness. For West Africa, changes in bee communities across disturbance gradients from savannah to agricultural land are mainly unknown. Our study aimed to assess the impact of land use patterns on bee communities in the department of Korhogo. We chose three sites of varying disturbance intensity (low, medium and high disturbance). Bees were caught using pan traps. Abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…This high representativeness might be attributed to the dominance of species belonging to this family in open and/ or secondary vegetation (Bárbola & Laroca, 1993). Our results are consistent with those of Eardley et al (2010) and Coulibaly et al (2023) in West Africa, who showed that the Halictidae family is the most diversified in sub-Saharan Africa. However, the used methodological approach and material with yellow pan traps might also maximised the sampling of species belonging to family Halictidae in comparison to Apidae and Megachilidae (Cane et al, 2000).…”
Section: Discussionsupporting
confidence: 94%
“…This high representativeness might be attributed to the dominance of species belonging to this family in open and/ or secondary vegetation (Bárbola & Laroca, 1993). Our results are consistent with those of Eardley et al (2010) and Coulibaly et al (2023) in West Africa, who showed that the Halictidae family is the most diversified in sub-Saharan Africa. However, the used methodological approach and material with yellow pan traps might also maximised the sampling of species belonging to family Halictidae in comparison to Apidae and Megachilidae (Cane et al, 2000).…”
Section: Discussionsupporting
confidence: 94%